2017
DOI: 10.1111/1556-4029.13716
|View full text |Cite
|
Sign up to set email alerts
|

Citrate Content of Bone as a Measure of Postmortem Interval: An External Validation Study

Abstract: The postmortem interval (PMI) of skeletal remains is a crucial piece of information that can help establish the time dimension in criminal cases. Unfortunately, the accurate and reliable determination of PMI from bone continues to evade forensic investigators despite concerted efforts over the past decades to develop suitable qualitative and quantitative methods. A relatively new PMI method based on the analysis of citrate content of bone was developed by Schwarcz et al. The main objective of our research was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…PMI estimation often relies on visual assessment of gross morphological changes of the body during decomposition, even though the rate of these changes is known to be highly variable. , Accuracy of the PMI estimation decreases as decomposition progresses, and interobserver reliability differs depending on the method and the experience of the researcher. , Biochemical techniques have shown promising results in the search for a precise and accurate method to estimate late PMI in human bone; however, these methods are yet to be validated for use in forensic contexts. …”
Section: Introductionmentioning
confidence: 99%
“…PMI estimation often relies on visual assessment of gross morphological changes of the body during decomposition, even though the rate of these changes is known to be highly variable. , Accuracy of the PMI estimation decreases as decomposition progresses, and interobserver reliability differs depending on the method and the experience of the researcher. , Biochemical techniques have shown promising results in the search for a precise and accurate method to estimate late PMI in human bone; however, these methods are yet to be validated for use in forensic contexts. …”
Section: Introductionmentioning
confidence: 99%
“…Kanz et al [ 33 ] observed that the degradation rate of citrate seemed to be slower in soil-buried bones compared to those deposited on the surface. Brown et al [ 34 ] did not find significant correlation between citrate content and PMI, although they did observe a decrease in citrate content with increasing PMI.…”
Section: Resultsmentioning
confidence: 94%
“…[ 31 ]. The use of citrate content in bone as a predictor of PMI has shown mixed results in various studies [ 31 , 32 , 33 , 34 ]. While certain studies have demonstrated a correlation between citrate content and PMI, other studies have not reached statistically significant results.…”
Section: Resultsmentioning
confidence: 99%